2022
DOI: 10.1097/mao.0000000000003611
|View full text |Cite
|
Sign up to set email alerts
|

The Outcome of Cochlear Implantations in Deaf-Blind Patients: A Multicenter Observational Study

Abstract: Objective: This multicenter study aimed to evaluate the auditory and speech outcomes of cochlear implantation (CI) in deaf-blind patients compared with deaf-only patients. Study Design: Retrospective cohort study. Setting: Multiple cochlear implant centers. Patients: The current study was conducted on 17 prelingual deaf-blind children and 12 postlingual deaf-blind adults who underwent CI surgery. As a control group, 17 prelingual deaf children and 12 postlingual deaf adults were selected. Intervention: Cochlea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…A recent multi-institutional study comparing cochlear implant outcomes in deaf–blind and deaf-only children showed no significant differences in Categories of Auditory Performance scores at 12 and 24 months postimplantation. However, deaf–blind children exhibited lower speech intelligibility rating scales and word recognition scores compared with deaf-only children ( Daneshi et al, 2022 ).…”
Section: Discussionmentioning
confidence: 93%
“…A recent multi-institutional study comparing cochlear implant outcomes in deaf–blind and deaf-only children showed no significant differences in Categories of Auditory Performance scores at 12 and 24 months postimplantation. However, deaf–blind children exhibited lower speech intelligibility rating scales and word recognition scores compared with deaf-only children ( Daneshi et al, 2022 ).…”
Section: Discussionmentioning
confidence: 93%